A technique for the detection of liquid slip at a load-bearing, high shear contact - Choo,JH; Spikes,HA; Ratoi,M; Glovnea,RP; Forrest,A (2005)
This research aims to exploit the physical phenomenon of simple liquids slipping against very smooth solid surfaces, to create a new type of bearing where the lubricant slips against one surface but not the other. To demonstrate the feasibility of this idea, a special test rig capable of measuring milli-Newton forces has been employed to measure friction in high-speed, sliding contacts between a steel roller and sapphire window, lubricated by hexadecane. Sapphire was made either lyophobic by coating with a self-assembled silane monolayer, or lyophilic by O2-plasma cleaning. The roller was made lyophilic. A significant reduction in friction was achieved with lyophobic sapphire but not with lyophilic sapphire. This reduced friction is believed to result from lubricant slip against the lyophobic surface. One possible application of such a bearing will be in microsystems and devices. Copyright © 2005 by ASME.